2021
DOI: 10.1186/s12902-021-00688-8
|View full text |Cite
|
Sign up to set email alerts
|

Acacetin ameliorates insulin resistance in obesity mice through regulating Treg/Th17 balance via MiR-23b-3p/NEU1 Axis

Abstract: Background The role of miR-23b-3p in insulin resistance (IR) remained poorly understood. Methods After acacetin injection, obesity-induced IR model was constructed with or without miR-23b-3p upregulation and Neuraminidase 1 (NEU1) overexpression in mice. Body weight, serum metabolite and fat percent of the mice were measured. Tests on oral glucose and insulin tolerance were performed, and inflammatory cytokines C-reactive protein (CRP), Interleukin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…KDM7A [61], LMNA (lamin A/C) [62], PFKFB3 [63], NEU1 [64], DUSP22 [65], ADORA2B [66], CRTC2 [67], GRN (granulin precursor) [68], CTSD (cathepsin D) [69], IGFBP4 [70], SMYD2 [71], OSM (oncostatin M) [72], INVS (inversin) [73], ANKFY1 [74], SEMA4D [75], PPM1A [76], IFNG (interferon gamma) [77], CTBP1 [78], ATP6 [79], COX2 [80], RPS19 [81], COX1 [82] and TLK1 [83] are potential biomarkers for the detection and prognosis of renal diseases. A previous study reported that LXN (latexin) [84], LMNA (lamin A/C) [85], PFKFB3 [86], NEU1 [87], TBK1 [88], GRN (granulin precursor) [89], CTSD (cathepsin D) [90], ACADS (acyl-CoA dehydrogenase short chain) [91], IRF7 [92], S1PR1 [93], ZAP70 [94], IDH1 [95], IL15 [96], PIK3R1 [97], OSM (oncostatin M) [98], SOCS3 [99], USP21 [100], CEP19 [101], KDM2A [102], TP53 [103], BRD2 [104], ATP6 [105], BRD4 [106], COX2 [107], RPS6 [108], ND2 [109], CYTB (cytochrome b) [110] and COX1 [111] are altered expressed in obesity. Altered expression of BCL3 [112], TRAF2 [113], NEU1 [114], SNAP29 [115], AGPAT2 [116], LPCAT3 [117], ADORA2B [118], CTSD (cathepsin D) [119], ACADS (acyl-CoA dehydrogenase short chain) [120], ACAD9 [121], E4F1 [122], IRF7 [123], TAF1 [124], S1PR1 [125], RASSF1 [126], ELAC2 [127], RNF146 [128], COX15 [129], SMYD2 [130], IDH1 [131], MTO1 [132], IL15 [133], PIK3R1 [13...…”
Section: Discussionmentioning
confidence: 99%
“…KDM7A [61], LMNA (lamin A/C) [62], PFKFB3 [63], NEU1 [64], DUSP22 [65], ADORA2B [66], CRTC2 [67], GRN (granulin precursor) [68], CTSD (cathepsin D) [69], IGFBP4 [70], SMYD2 [71], OSM (oncostatin M) [72], INVS (inversin) [73], ANKFY1 [74], SEMA4D [75], PPM1A [76], IFNG (interferon gamma) [77], CTBP1 [78], ATP6 [79], COX2 [80], RPS19 [81], COX1 [82] and TLK1 [83] are potential biomarkers for the detection and prognosis of renal diseases. A previous study reported that LXN (latexin) [84], LMNA (lamin A/C) [85], PFKFB3 [86], NEU1 [87], TBK1 [88], GRN (granulin precursor) [89], CTSD (cathepsin D) [90], ACADS (acyl-CoA dehydrogenase short chain) [91], IRF7 [92], S1PR1 [93], ZAP70 [94], IDH1 [95], IL15 [96], PIK3R1 [97], OSM (oncostatin M) [98], SOCS3 [99], USP21 [100], CEP19 [101], KDM2A [102], TP53 [103], BRD2 [104], ATP6 [105], BRD4 [106], COX2 [107], RPS6 [108], ND2 [109], CYTB (cytochrome b) [110] and COX1 [111] are altered expressed in obesity. Altered expression of BCL3 [112], TRAF2 [113], NEU1 [114], SNAP29 [115], AGPAT2 [116], LPCAT3 [117], ADORA2B [118], CTSD (cathepsin D) [119], ACADS (acyl-CoA dehydrogenase short chain) [120], ACAD9 [121], E4F1 [122], IRF7 [123], TAF1 [124], S1PR1 [125], RASSF1 [126], ELAC2 [127], RNF146 [128], COX15 [129], SMYD2 [130], IDH1 [131], MTO1 [132], IL15 [133], PIK3R1 [13...…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune diseases comprise a diverse collection of pathological conditions originating from a dysregulated immune response to a self tissue or organ. As discussed above, NEUs play a critical role in the activity of Treg cells ( 289 , 290 ) suggesting the possible involvement of NEUs in the pathogenesis of autoimmunity. Further, MUC1 has been suggested as a checkpoint inhibitor on T cells ( 334 ), implicating MUC1, and possibly other membrane-bound mucins, in the development of autoimmune diseases.…”
Section: Neus and Mucs In Autoimmune Diseasesmentioning
confidence: 96%
“…CD4 + activated Treg (FoxP3 + CD62L − ) spleen cells expressed higher levels of NEU3 transcripts compared with resting Treg (FoxP3 + CD62L + ) and FoxP3 − cells, and overexpression of NEU3 in naïve CD4 + T cells upregulated FoxP3 expression. In a mouse model of obesity-induced insulin resistance, the percentages of CD4 + FoxP3 + Treg cells and NEU1 levels were decreased, while the percentages of CD4 + Th17 + cells and the levels of the NEU1-targeting microRNA, miR-23b-3p, were increased, all compared with nonobese controls ( 290 ). Administration of the anti-obesity phytochemical, acacetin, reversed these effects, while administration miR-23b-3p exacerbated the outcomes.…”
Section: Neus In Innate and Adaptive Immunitymentioning
confidence: 99%
“…For example, Wei et al described a possible amelioration in obesity-dependent IR by acacetin in a mouse model. Acacetin seems to down-regulate IL-17 and up-regulate Foxp3 expression, promoting Treg/Th17 balance via targeting miR-23b-3p/NEU1 axis [ 186 ]. Finally, a therapeutic effect of epigallocatechin-3-gallate, has been observed in obese mice, showing a significant reduction in weight, LDL-cholesterol and triglyceride levels.…”
Section: Treg/th17 Dysregulation and Gluco-metabolic Abnormalitiesmentioning
confidence: 99%